Biological control of pomegranate butterfly Deudorix livia Klug (Lepidoptera: Lycaenidae) - Al-Riyami, Abdulhamid (2022)
This thesis comprises a group of interconnected studies collectively aimed at evaluating and improving biological control of an economically important pest, the pomegranate butterfly Deudorix livia (Lepidoptera: Lycaenidae). In the Al Jabal Al Akhdar, ‘green mountain’ area in Oman, where this study took place, D. livia is attacked by egg parasitoids, principally Telenomus nizwaensis Polaszek (Hymenoptera: Scelionidae) which is indigenous and also two imported species Trichogramma brassicae Bezdenko, and Trichogramma evanescens Westwood, (Hymenoptera: Trichogrammatidae). The first chapter provides an overall introduction to the biology and ecology of the pest and its natural enemies.